O Programa de Autonomia Escolar: a avaliação dos gestores escolares - Abreu, André Batista de Albuquerque (2024)
This research was developed within the scope of the Professional Master's Degree in Public Policy Assessment (MAPP) at the Federal University of Ceará (UFC). This seeks to evaluate the School Autonomy Program (PAE) as an education financing policy in the municipality of Maracanaú. This public education financing policy, created in 2015, aims to provide better objective working conditions for schools in the municipal network, strengthening and expanding management autonomy, making the maintenance and conservation of equipment installations more effective and efficient, including when it comes to the provision of services that favor the development of the school's pedagogical work. Furthermore, the research aimed, in general, to evaluate the effectiveness of the PAE in a school in the municipality of Maracanaú from the managers' perspective. The specific objectives were: i) to map the PAE implementation process; and ii) analyze the difficulties experienced by school managers in implementing the PAE. The research adopted an in-depth evaluation proposal and methodological procedure focused on bibliographical analyzes of articles and theses published on the subject and analysis of documents, such as Laws and decrees prepared by the Department of Education (SME) and semi-structured interviews with Unit Managers Executors (UEx). Finally, the data collected points to a policy with a path based on the improvement and decentralization of the transfer of resources being used to improve the school and which, in the words of the Managers, demonstrate a program that is easy to access, well monitored and advised by the SME.